2008
DOI: 10.3113/fai.2008.1117
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Kinematics of the Salto Total Ankle Prosthesis

Abstract: These measured translations were relatively small and may suggest that the rotational portion of the motion was more dominant than translational and provided sufficient mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 62 publications
4
44
1
2
Order By: Relevance
“…A N U S C R I P T 8 measurements (Leszko et al 2008;Cenni et al 2013) and also in accordance with the reported increased laxity after total ankle replacement (Watanabe et al 2009). For the ME case, the axial loading was thus also displaced anteriorly.…”
Section: A C C E P T E D Msupporting
confidence: 84%
See 2 more Smart Citations
“…A N U S C R I P T 8 measurements (Leszko et al 2008;Cenni et al 2013) and also in accordance with the reported increased laxity after total ankle replacement (Watanabe et al 2009). For the ME case, the axial loading was thus also displaced anteriorly.…”
Section: A C C E P T E D Msupporting
confidence: 84%
“…Besides, since we had no information about the donor, we applied the same loading to all tibias, which is certainly not fully consistent with real life. The eccentric case simulated here covered reported extreme displacements of the mobile bearing (Siegler et al 2005;Reggiani et al 2006;Leszko et al 2008). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eccentric cases simulated here covered reported extreme displacements of the mobile-bearing insert (Siegler et al, 2005;Reggiani et al, 2006;Leszko et al, 2008). The main limitation of the model was the use of non-fresh cadaveric bone, which were perfused and conserved 4 years in a formaldehyde solution.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in Europe, the appearance of new-generation, mobile-bearing, cementless prostheses has renewed interest in TAA [5,11,24,33,48,[51][52][53]. The theoretical advantages of TAA compared with arthrodesis are maintaining joint ROM and restoring more normal kinematics in the hopes of providing the patient with greater comfort and better functional recovery [7,31,33,35,49]. The disadvantages are related to the risk of mechanical complications with failure sometimes requiring implant removal along with subsequent arthrodesis, which can be technically demanding and lead to a less satisfactory result than with primary arthrodesis [10,19,47].…”
Section: Introductionmentioning
confidence: 99%